Tax havens and reputational costs - DePaul, Adrienne; Murphy, Frank; Vernon, Mary E. (Journal of Accounting and Economics, 2025)
In 2017, the European Commission (EC) published a list of non-cooperative tax havens. We study whether country-level tourism and foreign direct investment (FDI) change as a result of this list. Consistent with a reputational cost of the EC’s “name and shame” campaign, there is a modest reduction in EU tourism among listed countries compared to unlisted ones. This relative reduction is concentrated among tourists from countries that view cheating on taxes as less justifiable. In contrast, listed countries experience a general increase in FDI following the list, a benefit potentially offsetting the costs of reduced tourism.